Effect of Magnetized water and the pesticides Nominee and Rainbow on some growth parameters of rice var. Amber 33 Oryza sativa - Alwan, Sabah Latif; AL-Shebly, Hayder Azeez Ali; Ali, Amel Ajel; AL-Ghazali, Noor A. (Journal of Kerbala for Agricultural Sciences, 2018)
Experiment was conducted during the growing season of summer 2014 in a rice field at Al-Hira district in the province of Najaf to examine two factors, water type (magnetized MW and regular RW) and herbicide (Nominee and Rainbow at full and half of the recommended dose) and their effects on rice growth parameters including plant height, number of branches, fresh and dry weight. The experiment was two factorial base on Randomized Completely Block Design (RCBD) with three replicates. Results showed significant differences among all treatments in the experiment. The MW treatment significantly resulted in higher values of all parameters tested compared to the RW and weedy treatments, respectively. However, values of tested plant parameters were higher in both herbicides treatments with no significance compared to those of the MW treatment but at the same time were significantly much higher where compared to other treatments. Comparison between the herbicides showed that Nominee resulted in higher, but not significant, growth parameters compared those of the herbicide Rainbow. While, interaction among all treatments showed that the best results were from MW interacted with Nominee over other interaction treatments. Magnetized water in this study was approver to be effective treatment in supporting all growth parameters in rice crop fields.